Design of wastewater treatment plants in hot and cold climates. - (:unkn) unknown (My University, 2019)
The design of wastewater and sludge treatment plants under deviating wastewater and climatic conditions in other countries requires an amendment of existing design rules compliant to the DWA Set of Rules, which have been primarily developed for Central European conditions. This concerns, for example, the consideration of high or low wastewater temperatures, increased salt content or special discharge requirements. Within the framework of the EXPOVAL research project funded by the Federal Ministry of Education and Research (BMBF), internationally applicable design approaches have been developed. The results have been prepared for this volume in the form of internationally applicable design approaches and supplement the DWA Set of Rules accordingly. The new and extended design approaches include activated sludge plants, trickling filter systems and wastewater ponds, UASB-reactors, plants for anaerobic sludge stabilisation and solar sewage sludge drying, aeration systems and the elimination of helminth eggs. Practical calculation examples are presented for all processes. In addition to the extension and adaptation especially to different temperature conditions, the design approaches in this volume were uniformly converted to the internationally widespread monitoring practice by means of daily average values and to the chemical oxygen demand (COD) for the cleaning objective of carbon degradation.
Keywords: Siedlungsabwasser; Abwasser; Abwasserbehandlung; Abwasserreinigung; Reinigungsverfahren; Biologisches Verfahren; Kläranlage; Vorbehandlung; Belebungsanlage; Belüftungsanlage; Klärschlamm; Klärschlammtrocknung; Anlagenplanung; Bemessung; Kennzahl; Tropfkörperanlage; Anaerobe Abwasserbehandlung